Dilemmas of political correctness - Moller, D (Oxford Uehiro Centre for Practical Ethics, 2016)
Debates about political correctness often proceed as if proponents see nothing to fear in erecting norms that inhibit expression on the one side, and opponents see nothing but misguided efforts to silence political enemies on the other.1 Both views are mistaken. Political correctness, as I argue, is an important attempt to advance the legitimate interests of certain groups in the public sphere. However, this type of norm comes with costs that mustn’t be neglected–sometimes in the form of conflict with other values we hold dear, but often by creating an internal schism that threatens us with collective irrationality. Political correctness thus sets up dilemmas I wish to set out (but not, alas, resolve). The cliché is that political correctness tramples on rights to free-speech, as if the potential loss were merely expressive; the real issue is that in filtering public discourse, political correctness may defeat our own substantive aims.